Body, health, and consumer society: the social construction of a healthy body - Santos, Manoel Antônio dos; Oliveira, Vitor Hugo de; Peres, Rodrigo Sanches; Risk, Eduardo Name; Leonidas, Carolina; Oliveira-Cardoso, Érika Arantes de (Saúde e Sociedade, 2019)
Although the articulation between body, health, and the political-economic context is extremely complexandmediatedbyheterogeneousprocesses, itis possible to problematize the discourse on body and health produced by mass media. The purpose of this study was to present some reflections on contemporary discourses and practices about health, focusing on body aspects and the relationship between body aesthetics and the individual’s well-being. The argumentative line to be developed advocates that, in the discursive network disseminated by the great media, the concept of health is intimately tied to the consumer market. In this essay, some media discourses on health are analyzed,in orderto understand aspects of the symbolic market that is organized based on health signs. The construction of the “healthy body” is thematized and problematized through the chosen theoreticalroute.In the newApollonian ideal emerging in contemporaneity, the body is a moldable object, to be cultivated by Spartan diets and eating habits, educated in exhaustive sessions of physical exercises,modeled by anabolic substances, corrected by plastic surgery with aesthetic purpose, and regulated by sociocultural standards that aim to achieve the immortality masked in the myth of eternal youth. To improve health care, professionals must understand the transformations that affect the image of the body valued in the contemporary era.